The Impact of Global Climate Change on Environmental Migration in the Asia Pacific Region - Untari Narulita Madyar Dewi (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
Climate migration is an issue that has re-emerged along with the increasing threat of natural disasters and climate change. The complexity of international migration issues today is not only related to demographic factors, conflict, war, and economic factors. However, the implications of global climate change can become push and pull factors on the migration process. This study aims to find out the correlation between international migration issues and climate change that occurs in the Asia Pacific region. The theoretical frameworks used are the theory of international migration (Everett S. Lee) and the conceptual 'environmental migration' (Graeme Hugo). The research method used is qualitative research by prioritizing data collection based on literature studies and internet-based research. The results of this study show that there is a high risk due to climate change that must be faced by countries in the Asia Pacific region and the driving factors of migrating people in the Asia Pacific region are interpreted as mitigation measures from the threat of natural disasters.